2017
DOI: 10.3390/en10101622
|View full text |Cite
|
Sign up to set email alerts
|

Using Modularity to Reduce Complexity of Industrialized Building Systems for Mass Customization

Abstract: Abstract:It is widely known that industrialized building systems can positively impact construction projects in terms of efficiency, duration, safety, and quality. Although the use of industrialized building systems can potentially simplify the production process on-site, the complexity of the overall delivery system tends to be high, especially in engineered-to-order (ETO) environments, due to factors such as uncertainty related to goals and methods, conflicts between different trades on-site, and interdepend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 46 publications
0
31
0
4
Order By: Relevance
“…Therefore, the authors of this research paper detected mixed reported findings in the previous literature, that represent a gap for the current study as well as future researches as suggested by Squire et al (2004). Second, product modularity, the modular design is one technique for the masscustomisation approach, in which products are designed in the form of modules/components that are flexibly assembled/exchanged (Karlsson, 2002;Tu et al, 2004;Abdallah and Matsui, 2008;Heizer et al, 2017;Viana et al, 2017;Stevenson, 2018). This product modularity or modular design tactic satisfies both organisational functions, production and operations management in addition to marketing, because it saves manufacturing costs better than the customisation approach and augments customer delight more than the standardisation strategy (Duray, 2002;Heizer et al, 2017;Stevenson, 2018).…”
Section: Co-creating Modular Mass-customisation and Customer Valuementioning
confidence: 73%
“…Therefore, the authors of this research paper detected mixed reported findings in the previous literature, that represent a gap for the current study as well as future researches as suggested by Squire et al (2004). Second, product modularity, the modular design is one technique for the masscustomisation approach, in which products are designed in the form of modules/components that are flexibly assembled/exchanged (Karlsson, 2002;Tu et al, 2004;Abdallah and Matsui, 2008;Heizer et al, 2017;Viana et al, 2017;Stevenson, 2018). This product modularity or modular design tactic satisfies both organisational functions, production and operations management in addition to marketing, because it saves manufacturing costs better than the customisation approach and augments customer delight more than the standardisation strategy (Duray, 2002;Heizer et al, 2017;Stevenson, 2018).…”
Section: Co-creating Modular Mass-customisation and Customer Valuementioning
confidence: 73%
“…The construction industry is already using prefabricated building parts and modules, which enable development and testing before realisation. Efficiency during construction can potentially increase with prefabricated parts or modules produced off site [6]. Production of building parts on or off site with 3D printing of different materials (i.e., additive manufacturing) can adapt and optimise constructions for specific purposes [3].…”
Section: Automated and Industrial Techniquesmentioning
confidence: 99%
“…Definition of configurations based on data from operational use can prolong building lifecycles and increase usability [5]. Automated construction methods can improve efficiency and accuracy during production [6]. In the world, the construction industry accounts for 11% of the overall emissions and 6% of the energy consumption [7].…”
Section: Introductionmentioning
confidence: 99%
“…The link between construction modularity and supply chain integration can, according to Pero et al (2015), be traced back to Northern Europe's use of wooden houses and the Japanese house building industry's systematic use of non-volume and volume pre-assembled modules. In a case study of two American construction companies, Viana et al (2017) found that both case companies use a modular supply chain design to support the construction of modular buildings.…”
Section: Construction Supply Chainsmentioning
confidence: 99%